Identification and characterization of the hemoglobin‐binding domain of hemoglobin receptor in Leishmania. Issue 4 (2nd January 2021) - Rastogi, Ruchir; Verma, Jitender Kumar; Singh, Vijay; Krishnamurthy, Ganga; Sood, Chandni; Kapoor, Anjali; Kumar, Kamal; Ansari, Irshad; Mukhopadhyay, Amitabha
Abstract : Leishmania internalize hemoglobin (Hb) via a specific receptor (HbR) for their survival. To identify the Hb‐binding domain of HbR, we cloned and expressed several truncated proteins of HbR and determined their ability to bind Hb. Our findings reveal that 90% of Hb‐binding activity is retained in HbR 41–80 in comparison with HbR 1–471 . We synthesized a 40 amino acid peptide (SSEKMKQLTMYMIHEMVEGLEGRPSTVRMLPSFVYTSDPA) corresponding to HbR 41–80 and found that it specifically binds Hb. Subsequently, we found that the HbR 41–80 peptide completely blocks Hb uptake in both promastigote and amastigote forms of Leishmania and, thereby, inhibits the growth of the parasite. These results demonstrate that HbR 41–80 is the Hb‐binding domain of HbR, which might be used as a potential therapeutic agent to inhibit the growth of Leishmania . Abstract :